Acquired Immune Defi ciency Syndrome mortality rate in Thailand - Sriwattanapongse, Wattanavadee; Prasitwattanaseree, Sukon (Biomedical Sciences and Clinical Medicine, 2024)
Objective Acquired Immune Deficiency Syndrome (AIDS) has been a leading cause of morbidity in Thailand for many years. The objective of this study was to model and forecast the AIDS mortality rate in Thailand using data from death certificate reports. Methods A retrospective analysis of the AIDS mortality rate was conducted. The data were obtained from the national vital registration database for a 10-year period, from 2000 to 2009, provided by the Ministry of the Interior, and coded as cause-of-death using ICD-10 by the Ministry of Public Health. Multivariate linear regression was used for modeling and forecasting age-specific AIDS mortality rates in Thailand. Results AIDS mortality increased with increasing age in each gender and it also was higher in the northern and southern provinces. The trend of AIDS mortality remained stable in most age groups, but decreased in others after 2003. AIDS mortality was highest in males aged 30-39 years. Conclusion The multivariate linear regression model was suitable for modeling and forcasting AIDS mortality in Thailand. There is a need for a sustained and long-term AIDS control measures to deal with a high AIDS burden rate in Thailand.